Pulmonary adenomatosis and maedi-visna in Ethiopian central highland sheep: a microscopic study - Woldemeskel, M.; Tibbo, Markos (Springer, 2010)
Microscopic examination of pneumonic lungs of the Ethiopian highland sheep (n = 35) was made and compared with the pneumonic lungs from ten sheep and 66 goats from the lowlands. Lesions compatible with sheep pulmonary adenomatosis (SPA; 8/35, 22.8%), and maedi-visna (MV; 9/35, 25.7%) were recorded only in sheep from the central highlands. Interstitial pneumonia (43.2%), bronchopneumonia (35.1%), and verminous pneumonia (6.3%) were recorded in both sheep and goats from the high- and the lowlands. SPA was documented for the first time in sheep from Ethiopia in this report. We believe that MV and SPA were introduced into Ethiopia through importation of exotic sheep. These infections should be considered in dealing with the diagnosis of respiratory diseases in all the sheep breeds in the central highlands and in the exotic and the crossbred sheep in the other parts of the country.